Analysis of the financial statements of two publicly traded companies in accordance with the financial effects presented in the pandemic period - Sereni , Andréa Stefânia; Pastre , Fauston; Pommer , Viviani Maria; Garcia , Elias (Seven Editora, 2023)
This work aims to perform an economic and financial analysis of two large companies operating in the retail segment, located in Brazil, using for this the period referring to the years 2019, 2020 and 2021. To carry out this work it was necessary to develop a bibliographic review, where books were consulted that address the themes of financial statements and their analysis tools, extracting the information necessary to achieve the objectives proposed by the study. A qualitative research was carried out on the data collected in the balance sheets, and then analyzed the economic and patrimonial situation of the companies, through the Liquidity and Indebtedness Indices. These analyses took into account the Covid-19 pandemic, which generated a scenario of market fluctuations in companies, including positive results and sometimes justifying any negatives. The results were presented by tables. It was verified that through the analysis of the financial statements, it is possible to generate information about the economic and financial situation of the companies. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-018